Spatial variability of some soil properties around Zaria area, Kaduna state, Nigeria - Awwal, Yasin Agono; Fatihu, Ruqayyah Muhammad (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Introduction. Spatial variability of soil properties as influenced by both intrinsic and extrinsic factors, plays a pivotal role in agricultural productivity. Understanding this variability is critical for implementing site-specific management, which optimizes resource allocation while sustaining soil health. This study investigates the spatial variability of selected soil properties in agricultural fields around Zaria, Kaduna State, Nigeria, utilizing geostatistical techniques to provide insights for sustainable land management.Materials and Methods. The study was conducted in an 85-hectare area located in Zaria, Kaduna State. Seventy soil samples were collected using a grid sampling approach across 85 hectares. Following standard laboratory procedures, the samples were analysed for properties, including particle size distribution, bulk density (BD), pH, organic carbon (OC), and cation exchange capacity (CEC). Geostatistical analysis using Kriging interpolation and semivariogram modelling was employed to determine spatial dependence.Normal Distribution Test and Data Transformation. Laboratory data from the studied soil properties were tested for normality using the Ryan-Jover test, which revealed that most soil properties did not follow a normal distribution (P<0.05). Johnson trans-formation was hence applied to improve normality for reliable geostatistical modelling, as confirmed by the residuals from QQ Plots.Descriptive Statistics of Soil Properties. Clay content exhibited the highest variability (CV = 43.09%), ranging from 60 to 420 g kg-1. CEC showed moderate to high fertility potential, ranging from 6.33 to 25.50 cmol kg-1, while OC were generally rated low. BD and pH showed weak spatial variability (CV < 15%) due to the influence of intrinsic soil factors.Geostatistical Analysis of Soil Properties. Semivariogram modelling revealed strong spatial dependence for most soil properties (nugget ratio < 0.25), including BD, OC, and pH, suggesting intrinsic factors as key drivers. Spatial ranges varied across properties, with clay and CEC extending to 339.9 m and 347.6 m, respectively, while pH and BD showed shorter ranges of 85.4 m and 93.3 m. Spatial patterns in sand and clay demonstrated inverse relationships, as areas with higher clay contents exhibited higher CEC and pH levels.Spatial Distribution Maps. Kriging interpolation highlighted distinct spatial patterns, such as higher clay and CEC concentrations in specific zones, and lower pH in sandy areas, indicative of leaching effects. Maps showed that the spatial distribution of OC and BD is influenced by short-range processes, requiring localized management strategies.Conclusion. This study demonstrates the necessity of addressing spatial variability in soil management plans. Strong correlations between clay and CEC emphasize the critical role of texture in influencing soil fertility. Properties like OC and BD, with weak spatial dependence, demand immediate attention through targeted interventions such as organic amendments and improved tillage practices.